Strategies to Develop Long-Term Mortgage Credit - Jasinskaitė, Salomėja; Simanauskas, Leonas (Ekonomika, 1998)
The article deals with the reasons that are inhibiting long term-mortgage credit in Lithuania and provides the measures to decrease their influence. Long-tenn lending creates significant credit risk, interest rate risk, and liquidity risk that impede banks to make long-term loans. For the purpose to manage efficiently those risks and in such a way to increase banks’ possibilities to provide long-term loans it is suggested the innovations to be implemented in the Lithuanian credit market. The main provided instruments are as follows: introducing of variable interest rate mortgage loans, issuing of mortgage bonds by depository credit institutions, founding of specialised lenders - mortgage banks, refinancing mechanism of which should be based on the capital market securities, including mortgage bonds firstly.